Effectiveness of Solvent Vapor Annealing over Thermal Annealing on the Photovoltaic Performance of Non-Fullerene Acceptor Based BHJ Solar Cells - Datt, Ram (Sci Rep, 2019)
We explore two small molecules containing arms of dicyano-n-hexylrhodanine and diathiafulvalene wings terminated with benzothiadiazole linker, denoted as BAF-4CN and BAF-2HDT, respectively, as small molecule non-fullerene acceptors (SMNFAs) in organic solar cells. The proposed materials are mixed with a low band gap polymer donor PTB7-Th having broad absorption in the range of 400–750 nm to form solution-processed bulk heterojunctions (BHJs). The photoluminescence (PL) measurements show that both donor and acceptor can quench each other’s PL effectively, implying that not only electrons are transferred from PTB7-Th → SMNFAs but also holes are transferred from SMNFAs → PTB7-Th for efficient photocurrent generation. Furthermore, solvent vapor annealing (SVA) processing is shown to yield a more balanced hole and electron mobility and thus suppresses the trap-assisted recombination significantly. With this dual charge transfer enabled via fine-tuning of end-groups and SVA treatment, power conversion efficiency of approximately 10% is achieved, demonstrating the feasibility of the proposed approach.